Form and function: quantifying geomorphic heterogeneity and drivers in dryland non-perennial river corridors - Scamardo, Julianne E., author; Wohl, Ellen, advisor; McGrath, Dan, committee member; Morrison, Ryan, committee member; Rathburn, Sara, committee member (Colorado State University. Libraries, 2023)
Non-perennial rivers, including intermittent rivers and ephemeral streams, comprise the majority of drainage networks globally. However, ephemeral streams remain understudied compared to perennial counterparts, and the majority of extant studies focus on in-channel dynamics. Floodplains along perennial streams are known to host a high density of ecosystem functions, including the attenuation of downstream fluxes and provision of habitat to diverse flora and fauna. These functions are thought to be correlated to geomorphic heterogeneity, and studies of floodplain heterogeneity are emerging on perennial rivers. Here, I extend the conceptualization of floodplain function and heterogeneity commonly focused in perennial watersheds to dryland, ephemeral streams. Based on a synthesis of current literature identifying ephemeral stream floodplain characteristics in drylands, a set of floodplain styles emerge dependent on confinement and the presence of channelized flow. Functions related to attenuation and storage are typically concentrated in unconfined and channeled floodplains. The temporary storage of sediment and sub-surface water in ephemeral stream floodplains make them hotspots for biogeochemical cycling and hosts to richer, denser, and more diverse vegetation communities compared to surrounding uplands. Many functions of ephemeral stream floodplains are also found in perennial counterparts, but flashy flow regimes and high sediment loads in ephemeral streams can potentially impact rates and magnitudes of comparable processes and functions. Similar to perennial rivers, the diverse physical and ecological functions in ephemeral stream floodplains are thought to be related to spatial geomorphic heterogeneity. Although studies on the characteristics and drivers of geomorphic heterogeneity exist for perennial streams, similar studies in ephemeral streams are lacking. Geomorphic heterogeneity was therefore quantified along with potential drivers – including metrics related to geomorphic context and proxies for flood disturbance – to understand underlying processes in ephemeral river corridors. Geomorphic units were mapped in 30 unconfined river corridors within six non-perennial watersheds in Utah and Arizona, U.S. Landscape heterogeneity metrics – Shannon's Diversity Index, Shannon's Evenness Index, and patch density – were used to quantify geomorphic heterogeneity within each reach. Additionally, variables that potentially constrain or drive heterogeneity were quantified, including floodplain shape, grain size, large wood abundance, channel change and sediment storage times. Although heterogeneity positively correlated with metrics for morphology and disturbance (i.e., channel change and storage), statistical models suggest that morphologic context, particularly floodplain width, was a more important predictor for estimating geomorphic heterogeneity. Still, geomorphic units reflected aggradation processes indicative of a range of flood energies, suggesting a strong tie between heterogeneity and disturbance. Results suggest that non-perennial rivers with greater geomorphic heterogeneity may be resilient to changes in flood disturbance frequency or magnitude, but future studies investigating long-term temporal heterogeneity are needed. The lack of direct flux observations could also be restricting insight into how floods interact with large wood and vegetation, which are known to have complex relationships with geomorphic heterogeneity in perennial rivers. In the absence of flood observations, a hydro-morphodynamic model was developed to investigate changes to channel and floodplain morphology due to wood and vegetation in an ephemeral river corridor in southeastern Arizona, U.S. Three scenarios were modeled: the actual configuration of the river corridor; an experiment in which jams were removed; and an experiment in which vegetation was removed. Both large wood and vegetation effectively confined flow to the main, unvegetated channel, which became wider and deeper over the course of a single moderate flood. When isolating the impact of large wood, model results show that wood increases the magnitude of channel change created by vegetation, resulting in ±0.1 to 0.3 m of additional scour or aggradation. The simulated removal of vegetation resulted in more channel change than the removal of wood alone, partially because vegetation occupies a much greater area within the stream corridor than large wood. I propose a conceptual framework in which large wood could mediate sedimentation as well as the recruitment and growth of vegetation in ephemeral streams, contributing to the evolution of ephemeral stream morphology over time. Due to the ubiquity of dryland ephemeral streams, results of this research have the potential to influence watershed management globally. Wide, unconfined ephemeral stream floodplains and riparian forests could be targets for protection and restoration similar to current efforts in perennial rivers. Particularly in the context of future climate and land use changes, understanding the natural character, function, and heterogeneity of ephemeral stream floodplains highlights their physical and ecological importance in dryland landscapes.
Keywords: ephemeral stream; floodplain; dryland; geomorphic unit; flash flood